Analisis Pengelolaan Inventory Kayu Menggunakan Metode Economic Order Quantity pada UD. Sofie Furniture - Rifqi Subadil; Kusnadi Kusnadi (Fakultas Teknik, 2023)
The Economic Order Quantity (EOQ) method is utilized to determine the most efficient inventory management strategy that minimizes associated costs. A study was conducted at UD. Sofie Furniture, a wood industry company located in Karawang, addresses their difficulties in obtaining wood due to long delivery times from suppliers. The objective of this research was to determine the ideal ordering quantity for raw materials using the EOQ method, as well as to identify safety stock, reorder time (Reorder Point), and total inventory management costs at UD. Sophie Furniture. The application of the EOQ method has demonstrated its ability to optimize inventory management costs, including ordering and storage expenses, while additionally allowing the company to adjust the total inventory cost to IDR 4,105,959.99. It is therefore recommended that the company evaluate its wood inventory management policy using the EOQ method to ensure the purchase of wood is executed in an optimal manner, with a lower cost